2007
DOI: 10.1111/j.1532-5415.2007.01316.x
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculin Skin Test Reaction and Body Mass Index in Old Age Home Residents in Hong Kong

Abstract: In the elderly population, interpretation of TST should take into consideration the BMI of the individual. A positive TST according to one-step but not two-step testing was useful in predicting the development of active TB on follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 17 publications
1
19
0
Order By: Relevance
“…In the oldest age group there was no statistically significant change in the very high prevalence of TST positivity. Recent studies corroborate these findings revealing that TB infection in older populations has been stable or increasing in developing countries around the world, [30][31][32][33][34] making TB infection one of the most prevalent infections affecting older populations. 34 There were few differences in TST and tetanus results from 2005 11 to 2012.…”
Section: Discussionsupporting
confidence: 69%
“…In the oldest age group there was no statistically significant change in the very high prevalence of TST positivity. Recent studies corroborate these findings revealing that TB infection in older populations has been stable or increasing in developing countries around the world, [30][31][32][33][34] making TB infection one of the most prevalent infections affecting older populations. 34 There were few differences in TST and tetanus results from 2005 11 to 2012.…”
Section: Discussionsupporting
confidence: 69%
“…In the present study, both children [456 (30%)] and malnourished individuals [743 (49%)] were included and this could be a possible explanation for the diminished TST response owing to altered cellular- immunity in these subjects [20,21]. It was also observed that patients falling within the age group of 25–34 years had higher incidence rate as compared to pediatric patients.…”
Section: Discussionmentioning
confidence: 99%
“…Attention should also be paid to the elderly institutions due to the higher LTBI/TB prevalence in elderly congregate settings, which were widely observed in low-incidence countries like United States [8, 21, 63], and in intermediate TB burden regions like Hong Kong [6466]. With appropriate infection control measures, the risk of infection is only 0.6–1.2% with no cases of active disease, while the infection risk can reach 7.7% without measures [67].…”
Section: Discussionmentioning
confidence: 99%